(untitled) (Journal of the College of Basic Education, 2022)
The Arab-Islamic city has its own characteristics related to the ideology that it believes in, forms, and distinguishes it from the Western city that expresses its civilization, and governs the Arab concept of city capitals in the Islamic era. From other cities, the process of selecting cities for the Arab Islamic State is as old as the emergence and spread of Islam, as it began since the time of the Holy Prophet and his dissemination of the Islamic call. .